Chronic health risk comparison between China and Denmark on dietary exposure to chlorpyrifos. (February 2020) - Sang, Chenhui; Sørensen, Peter Borgen; An, Wei; Andersen, Jens Hinge; Yang, Min
Abstract: Chlorpyrifos is one of the most heavily used pesticides in domestic and agricultural insect prevention globally. Given the potential neurotoxicity of chlorpyrifos and its high detection rates in food and drinking water, health risks attributable to chlorpyrifos residue in Chinese drinking water and food in both China and Denmark were assessed in this study. Mixed left-censored handling models were used to deal with the non-detected values in chlorpyrifos concentrations. Results show that chronic exposure imputed to chlorpyrifos residue is much lower than the reference dose, and will thus not pose appreciable health risk to the consumer. Compared to the total exposure from chlorpyrifos in drinking water and food sources, chronic exposure from drinking water sources in China accounts for 0–4.4%. Health risk owing to chlorpyrifos in food within China is 6-7-fold higher than in Denmark, and this coincides with the fact that all application of chlorpyrifos is banned in Denmark, in contrast to China. However, the Danish consumers are still exposed from imported food items. The main health risk contributors in China are the food groups of Grains and grain-based products and Vegetable and vegetable products, while the main chronic health risk contributor in Denmark is the food group of imported fruit and fruit products. Graphical abstract: Image 1 Highlights: Whether to ban chlorpyrifos in the world is a controversial question. Chronic health risk of chlorpyrifos in China and Demark by oral intake is compared. Mixed left-censored handling models were used to deal with the non-detected values. The health risks in Danish foods are mainly attributable to imported fruits. The HQ for chlorpyrifos in Chinese food is 6-7-fold higher than in Danish food. Abstract : Chronic exposure due to chlorpyrifos residue in food in China is 6-7-fold higher than in Denmark.